Study of Market Indicators used for Technical Analysis - Srushti Dongrey (International Journal of Engineering and Management Research, 2022)
Anticipating and analyzing the stock market and the price movement is a challenging task as the nature of the stock prices is quite complicated, non-linear and dynamic. Examining the financial time series data and making decisions is the toughest job in stock market. These correct decisions help in improving the returns on investment and minimize the loss and risks incurred. Technical analysis has been a trading tool since the 18th century which is used by investors and traders to evaluate the investments, identify the trading opportunities and forecast the future stock prices movement by analyzing price trends, chart patterns and volume data. Many different statistical tools are available for the investors and traders for making decision in financial market and analyze the stocks intrinsic value on the basis of fundamentals like balance sheet, revenues, industry trends, economic indicators and consumer behavior. Technical analysis helps the traders and investors predict the market situations and build the gap between market price and intrinsic value of the stocks by applying the techniques of behavioural economics and statistics. Many technical indicators like Simple Moving Averages, Weighted Moving Average, Trend Indictors, Momentum indicators like Stochastic, Relative Strength Index, Commodity Channel Index and Volatility indicators like the Bollinger Bands, Average True Range and Volume indicators are commonly available to study the stock price movement. In this project, the importance and the application of market indicators for technical analysis in predicting stock price movement of large-cap, mid-cap and small-cap companies on BSE is researched.